Pinyin or no pinyin: does access to word pronunciation matter in the assessment of Chinese learners' vocabulary knowledge?. Issue 3 (27th May 2019) - Zhang, Dongbo; Lin, Chin-Hsi; Zhang, Yining; Choi, Yunjeong
ABSTRACT: This study examined the impact of providing access to word pronunciation on the assessment of L2 Chinese learners' vocabulary knowledge. Chinese heritage learners (HLs) and foreign language learners (FLs) studying in American universities undertook a computer-based test in which they had first to select a picture that represented the meaning of a target word presented in characters only, and then answer the same item presented in both characters and pinyin (i.e. the alphabetic system to facilitate the pronunciation of characters). The provision of pinyin substantially increased the test reliability for both groups of learners but the differences between the no-pinyin and pinyin conditions were less marked for FLs than HLs. In the no-pinyin condition, the groups showed no significant score difference, whereas in the pinyin condition, HLs significantly outperformed FLs. The proportion of HLs who successfully corrected their original choices following provision of pinyin was also notably higher. These findings suggest that provision of pinyin impacted the two groups differentially. Implications for vocabulary knowledge assessment for different types of Chinese learners are discussed.